Notes on internal medicine and internists in Cienfuegos - Alfredo Darío Espinosa Brito; Reinaldo José Pino Blanco (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
In the absence of previous evidence, the purpose of this work is to publicize the development of internal medicine and internists in Cienfuegos. It was realized through a process of reconstruction and analytical reflection, based on the review of available documents, records and references, complemented by the testimony of the authors' own experiences, active participants in the territory during the last five decades, as well as the contributions of the collaborators. In each of these epigraphs, the most important characteristics and results achieved at different stages of Internal Medicine and internists in Cienfuegos are presented, in the assistance, teaching and research and administrative aspects, so as an analysis of them. Sixty one references are cited and multiple publications are mentioned, theses, national awards and outstanding activities of internists from Cienfuegos. The five annexes presented show the result of a systematic formation of specialized human resources in Internal Medicine in the territory.